Increased 5-Lipoxygenase Immunoreactivity in the Hippocampus of Patients With Alzheimer's Disease - Ikonomovic, Milos D. (Histochemical Society, 2008)
The proinflammatory enzyme 5-lipoxygenase (5-LOX) is upregulated in Alzheimer's disease (AD), but its localization and association with the hallmark lesions of the disease, β-amyloid (Aβ) plaques and neurofibrillary tangles (NFTs), is unknown. This study examined the distribution and cellular localization of 5-LOX in the medial temporal lobe from AD and control subjects. The spatial relationship between 5-LOX immunoreactive structures and AD lesions was also examined. We report that, in AD subjects, 5-LOX immunoreactivity is elevated relative to controls, and its localization is dependent on the antibody-targeted portion of the 5-LOX amino acid sequence. Carboxy terminus–directed antibodies detected 5-LOX in glial cells and neurons, but less frequently in neurons with dystrophic (NFT) morphology. In contrast, immunoreactivity observed using 5-LOX amino terminus–directed antibodies was virtually absent in neurons and abundant in NFTs, neuritic plaques, and glia. Double-labeling studies showed a close association of 5-LOX–immunoreactive processes and glial cells with Aβ immunoreactive plaques and vasculature and also detected 5-LOX in tau immunoreactive and amyloid containing NFTs. Different immunolabeling patterns with antibodies against carboxy vs amino terminus of 5-LOX may be caused by post-translational modifications of 5-LOX protein in Aβ plaques and NFTs. The relationship between elevated intracellular 5-LOX and hallmark AD pathological lesions provides further evidence that neuroinflammatory pathways contribute to the pathogenesis of AD. (J Histochem Cytochem 56:1065–1073, 2008)